Pemberdayaan Ekonomi Masyarakat Melalui Pelatihan Olahan Bawang Merah Menjadi Makanan Variatif - Qonita Aprilia; Febby Esa Viantika M; Nisma Nurma Afida; Risma Melawati; Tiara Rizki Febriana (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The economic growth of the people of Sendangkulon Village, Kendal Regency, is greatly influenced by the harvest of shallots, which is the main commodity in the area. However, changes in the price of raw shallots often become a challenge for farmers. To overcome this problem, the Sendangkulon Village government collaborated with the Central Java Province Training and Cooperative Center and PT Sinergi Brebes Inovatif to initiate training on shallot processing. This training aims to increase the selling value of red onions by teaching people how to process them into value-added products, such as fried onions, onion crackers and chili sauce. Apart from that, this training also covers digital marketing techniques to help people market their processed products more effectively. This program is expected to increase the economic empowerment of the Sendangkulon Village community and reduce poverty levels. However, challenges remain, especially in mastering digital marketing which requires further socialization.